2011
DOI: 10.1007/bf03325767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aerodynamic configuration of a streamline box girder on bridge flutter and vortex-induced vibration

Abstract: Streamline box girders are widely applied in the design and construction of long-span bridges all over the world. In order to study the influence of modifications of aerodynamic configuration and accessory components on flutter and vortex-induced vibration (VIV), more than 60 cases were tested through a 1 50 scale section model. The test results indicates that the aerodynamic configuration and accessory components of streamline box girders can significantly affect the wind-induced vibration of bridge, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…In addition, all of the values of U cr of closed-box girders with α = 50° are much higher than those with α = 60°, which confirms that closed-box girders with a relatively sharper wind fairing angle have better flutter performances. It is noted that the flutter performance was not obviously improved when the β value was below 16° for the large angle of α = 60°, which is different from the results of the study of Wang et al (2011) [ 17 ].…”
Section: Flutter Performance Comparisoncontrasting
confidence: 93%
See 1 more Smart Citation
“…In addition, all of the values of U cr of closed-box girders with α = 50° are much higher than those with α = 60°, which confirms that closed-box girders with a relatively sharper wind fairing angle have better flutter performances. It is noted that the flutter performance was not obviously improved when the β value was below 16° for the large angle of α = 60°, which is different from the results of the study of Wang et al (2011) [ 17 ].…”
Section: Flutter Performance Comparisoncontrasting
confidence: 93%
“…The flap and fairing are often used to improve the aerodynamic stability of the bridge section [ 13 ]. Wang reached the conclusion that the flutter critical wind speed increases significantly and the VIV phenomenon disappears when the inclined angle of the lower inclined web turns below 16° for the 4th Nanjing Yangtze River Bridge [ 17 , 18 ]. Larsen and Wall [ 1 ] utilized three different bottom plate inclinations and also recommended an angle of around 15° to suppress vortex shedding vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative approach was the passive aerodynamic method, which employed accessory components on the bridges, such as guide vanes [5] and wing plates [12,13] to improve aerodynamic performance. It was found that the guide vanes were effective in suppressing vortex-induced vertical oscillations of the suspension bridge of the Great Belt Bridge, as reported in Larsen et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, considering that the aerodynamic behaviour of bridge decks is often remarkably affected by the presence of permeable fences [15][16][17] and that they are always present in working conditions, their influence on the flow organization is studied for the largest gap ratio. The paper is organized as follows: in Section 2, the setup used to extract experimental data is briefly reported.…”
Section: Introductionmentioning
confidence: 99%